The features of the biomechanics in football players on the anatomical structures of the groin - Anastasia Omelchenko; Oleksandr Ioffe; Oleksandr Kovalchuk; Natalia Nehria; Boris Reznychenko; Mykola Kryvopustov; Valentyn Sergiіenko; Vladyslav Danilchenko; Yuriy Dibrova; Oleksandr Stetsenko; Yuriy Tsiura; Stepan Kindzer; et al. (Bogomolets National Medical University, 2021)
Pain in the lower abdomen and groin can occur in athletes who perform sharp lower extremity movement during training or sports, make sharp turns and change direction of the trunk movement as well as lower extremity acceleration/deceleration. An excessive load during the sports game can disturb the biomechanics of the player's movements. A precise localization of damaged tissues can improve for the diagnosis, determining treatment and forecasting the time of return to sports. The aim was to estimate the importance of the football biomechanics movement for the anatomy of the groin and to determine the anatomical features of the groin in football players with sports hernia. We analysed the thickness and length measurements on MRI of the rectus abdominis muscle in 51 football players of professional and amateur clubs aged 17 to 33 years with groin pain who were treated at the Kyiv Clinical City Hospital №3 for the period 2014-2020. In the second stage of the study, we investigated the peak force of the abdominal muscles (rectus abdominis, external oblique abdominal muscles) and the adductor muscles of both lower extremities using the microFET2 dynamometer for 4 groups of football players. The first group of the study includes 15 football players of professional clubs with sports hernia who had received conservative treatment, the partipants of the second group are 36 football players after laparoscopic hernioplasty, the third group consisted of 54 healthy young football players and 11 teenage footballers. In the third stage of the study, a formula was substantiated, according to which we calculated the acceleration of the lower extremity when kicking the ball. The results of the study demostrate that the disruption of the lower extremity biomechanics during kicking the ball cause the appearance of sports hernia in football players. An axial MRI scan of groin areas of football players with sports hernia represented changes in the lateral edge of the rectus abdominis. The groin pain syndrome of football players with sports hernia includes three pathogenetic mechanisms of development: disruption of the biomechanics, muscle imbalance and microtrauma and inflammation.